Global Positioning System activity profile in touch rugby: Does training meet the match-play intensity in a two-day international test match series? - Chow, C.-C. G. (Journal of Sports Science & Medicine, 2020)
This study quantified the match-play activity profiles of international touch rugby and different positional physical outputs in comparison with training specificity. Between November 2019 and January 2020, 82 half-matches and 173 training global positioning system data from 16 national male touch rugby players (mean ± SD: age 23.71 ± 3.90 years, height 1.73 ± 0.05 m, weight 65.38 ± 9.08 kg, touch rugby training experience 6.09 ± 3.31 years) were recorded. The distance covered by wings in half-match (1676.66 ± 444.80 m) was more than that of link (1311.35 ± 223.59 m) and middle (1383.52 ± 246.55 m) by a large effect (partial Eta2 = 0.19), which was mainly attributed to walking and jogging (< 4.00 m·s-1). Meanwhile, the middles covered more running distance (4.00-5.50 m·s-1) than other positions. No significant positional group difference was observed for distance covered >5.50 m·s-1, maximum velocity, and the ratio of acceleration and deceleration in matches. Training intensity was close to the match-play outputs only for the high-speed running distance at = 5.50 m·s-1. However, the training activity pattern consistently showed a disparity with the match-play outputs, in terms of shorter normalized training distance covered, less recovery distance covered at = 5.50 m·s-1, higher maximum velocity, and heavier weighting to acceleration in training activities. The current study highlights for the first time that in-match deceleration capacity and active recovery pacing strategy may be essential to touch rugby players. The data provided practitioners a deeper understanding of the physical demands of national touch rugby and allowed them to align the training with the match-play intensity.